Impact of deep sedation on the accuracy of hepatic and portal venous pressure measurements in patients with cirrhosis. Issue 1 (13th June 2013) - Reverter, Enric; Blasi, Annabel; Abraldes, Juan G.; Martínez‐Palli, Graciela; Seijo, Susana; Turon, Fanny; Berzigotti, Annalisa; Balust, Jaume; Bosch, Jaume; García‐Pagán, Juan C.
Abstract Background & Aims Measurement of the hepatic venous pressure gradient (HVPG) offers valuable prognostic information in patients with cirrhosis. In specific circumstances, (children, agitated patients, TIPS placement) deep sedation is required. This study aims to assess the impact of deep sedation on the accuracy of hepatic/portal pressure measurements. Methods Forty‐four patients were included. Measurements of baseline HVPG (n = 30), HVPG response to i.v. propranolol (n = 11), portal pressure gradient (PPG) after TIPS (n = 27) and of cardio‐pulmonary pressures (n = 25) were obtained in awake conditions and under deep sedation with propofol and remifentanil. Results During deep sedation, a marked oscillation within respiratory cycle was observed in abdominal pressures. End‐expiratory sedated HVPG showed a better agreement with awake HVPG (intra‐class correlation coefficient – ICC 0.864) than end‐inspiratory HVPG (ICC 0.796). However, in almost half of the patients both values differed by more than 10%. Accuracy was not improved by using mean HVPG along the respiratory cycle. Similarly, changes in HVPG caused by propranolol while under sedation had a poor agreement to those obtained in awake conditions. Indeed, about a half of patients were misclassified according to the 10% HVPG reduction target. After TIPS, PPG values obtained under sedation were significantly different to awake PPG, usually underestimating the awake value. The systemic hemodynamic changes induced by sedation were not associated to a greater variability of PPG/HVPG measurements. Conclusion Deep sedation with propofol and remifentanil adds substantial variability and uncertainty to HVPG/PPG measurements. This must be considered when using these values to estimate prognosis, or targeting HVPG/PPG reductions.